Stratification of Patients With Stage IB NSCLC Based on the 8th Edition of the American Joint Committee on Cancer (AJCC) Staging Manual - Wu, Lei-Lei; Liu, Xuan; Jiang, Wen-Mei; Huang, Wei; Lin, Peng; Long, Hao; Zhang, Lan-Jun; Ma, Guo-Wei (Frontiers in Oncology, 2020)
Objective: To assess the postoperative prognosis of patients with stage IB non-small cell lung cancer (NSCLC), using a prognostic model (PM). Methods: Patients with stage IB of NSCLC from the two academic databases {the Surveillance, Epidemiology, and End Results [SEER-A, N = 1,746, (training cohort)], Sun Yat-sen University Cancer Center [SYSUCC, N = 247, (validation cohort)] and SEER-B (N = 1,745)} who had undergone lung surgery from 2001 to 2015 were enrolled. The primary clinical endpoint was cancer-specific survival (CSS). Covariate inclusion of prognostic indicators was carried out using a multivariable two-sided P-value < 0.05. We identified and integrated significant prognostic factors for survival in the training cohort to build a model that could be validated in the validation cohort. We used univariate analysis to evaluate the utilized ability of PM in the different races/ethnicities. Results: CSS discrimination in the PM was comparable in both the training and validation cohorts [C index= 0.66(SEER-A), 0.67(SYSUCC) and 0.61(SEER-B), respectively]. Discretization with a fixed PM cutoff of 291.5 determined from the training dataset yielded low- and high-risk subgroups with disparate CSS in the validation cohort (training cohort: hazard ratio [HR] 2.724, 95% confidence intervals [CI], 2.074–3.577; validation cohort: SEER-B HR 1.679, 95% CI, 1.310–2.151, SYSUCC HR 3.649, 95% CI 2.203-6.043, all P < 0.05). Our five-factor PM was able to predict CSS; 48-month CSS was 87% in the low-risk subgroup vs. 69% in the high-risk subgroup for the training cohort, while in the validation cohort, they were 80% vs. 73%(SEER-B) and 84% vs. 60% (SYSUCC), respectively. In addition, the results showed that PM with all unadjusted HR > 1 was a significant risk prognostic indictor in white men (P < 0.001), Chinese people (P < 0.001), and other races (P = 0.012). Conclusion: We established and validated a PM that may predict CSS for patients with IB NSCLC in different races/ethnicities, and thus, help clinicians screen subgroups with poor prognosis. In addition, further prospective studies and more cases from different regions are necessary to confirm our findings.